An SCR denitrification process for treating phenylenediamine waste gas

By using modified kaolin-supported vanadium titanium catalyst and ammonia injection technology in SCR technology, the shortcomings of traditional SCR technology in temperature window and catalyst stability are solved, and efficient NOx removal and long life of the catalyst are achieved.

CN119236675BActive Publication Date: 2025-03-11ANHUI HUAERTAI CHEM IND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411783177.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Traditional SCR technology has narrow and high operating temperature windows in actual application, and other particulate matter and sulfides will cause catalyst deactivation and poisoning, making it difficult to effectively treat NOx in phenylenediamine exhaust gas.

Method used

Using a modified kaolin-supported vanadium-titanium catalyst, by injecting ammonia into the flue gas upstream of the catalyst, and using a modified kaolin-supported vanadium-titanium catalyst to perform SCR denitrification, the catalyst's water resistance and sulfur resistance are improved, and the low-temperature catalytic activity and temperature window are enhanced.

Benefits of technology

The denitrification efficiency in phenylenediamine waste gas treatment was significantly improved to reach 98.3%, and good denitrification performance was maintained within the medium and low temperature range, reducing the risk of catalyst deactivation and poisoning.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention discloses an SCR denitration process applied to the treatment of phenylenediamine waste gas, which belongs to the technical field of industrial waste gas treatment and comprises the following steps: injecting a reducing agent into the flue gas upstream of the catalyst, and performing SCR denitration using a modified kaolin-supported vanadium-titanium catalyst. The present invention provides an SCR denitration process applied to the treatment of phenylenediamine waste gas, which can significantly improve the denitration efficiency in the treatment of phenylenediamine waste gas by introducing a modified kaolin-supported vanadium-titanium catalyst prepared by a specific method into the SCR denitration process, and the denitration efficiency can reach 98.3%, which greatly reduces the emission of NOx in the production of phenylenediamine, and effectively improves the quality of the surrounding environment. The catalyst introduced by the present invention not only has good water resistance and sulfur resistance, but also presents good low-temperature catalytic activity and a wide temperature window, and at the same time well avoids the situation where other particulate matter and other sulfides cause catalyst deactivation and poisoning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of industrial waste gas treatment, and in particular relates to an SCR denitration process applied to phenylenediamine waste gas treatment. Background Art

[0002] During the preparation of phenylenediamine, nitrogen oxides (NOx) are produced. NOx is one of the sources of air pollution. NOx is a colorless and odorless gas, but it can react with water, oxygen, etc. in the atmosphere to form acidic substances such as nitric acid and nitrous acid, leading to the formation of acid rain. NOx can also react with volatile organic compounds in the atmosphere to form photochemical smog, which seriously affects air quality. The most effective and mature technology commonly used in industry to remove NOx from flue gas is selective catalytic reduction technology (SCR).

[0003] SCR denitrification technology is a highly efficient NOx removal technology. Its principle is to use a reducing agent (such as ammonia) to react with NOx in the flue gas under the action of a catalyst to reduce it to harmless nitrogen and water. SCR denitrification technology has the advantages of high denitrification efficiency, good selectivity, and a wide range of applications. It is widely used in flue gas treatment in the power, metallurgy, chemical and other industries.

[0004] However, the most important part of traditional SCR technology is the catalyst, which is installed upstream of the particulate matter collector and flue gas desulfurization device. As a result, SCR technology has a narrow and high operating temperature window (300-400°C) in actual application to ensure a high conversion rate of NOx. At the same time, other particulate matter and other sulfides can also cause deactivation and poisoning of the catalyst.

[0005] Based on this, we proposed an SCR denitrification process for the treatment of phenylenediamine waste gas, hoping to solve the shortcomings of the existing technology. Summary of the invention

[0006] The purpose of the present invention is to provide an SCR denitration process for treating phenylenediamine waste gas in view of the existing problems.

[0007] The present invention is achieved through the following technical solutions:

[0008] An SCR denitration process for treating phenylenediamine waste gas comprises the following steps:

[0009] A reducing agent is sprayed into the flue gas upstream of the catalyst, and SCR denitrification is performed using a modified kaolin-supported vanadium-titanium catalyst.

[0010] As a further technical solution, the reducing agent is ammonia.

[0011] As a further technical solution, the preparation method of the modified kaolin-supported vanadium-titanium catalyst is:

[0012] Dissolve ammonium metavanadate in deionized water, stir for 1-2 hours, then add TiO 2 The powder was fully stirred for 2-3 hours, then the modified kaolin dispersion was added, and the mixture was placed in an ultrasonic generator and ultrasonically treated at 80°C for 4-5 hours. After evaporating excess water, the mixture was placed in a muffle furnace and calcined at 500-600°C to obtain the modified kaolin-supported vanadium-titanium catalyst.

[0013] As a further technical solution, the mass fraction of ammonium metavanadate in the modified kaolin-supported vanadium-titanium catalyst is 3-4%, the mass fraction of modified kaolin is 8-12%, and the rest is TiO 2 ;

[0014] When ammonium metavanadate is dissolved, ethanolamine is added as a co-solvent.

[0015] As a further technical solution, the preparation method of the modified kaolin dispersion is:

[0016] Add the modified kaolin into distilled water, and use a magnetic stirrer to fully mix the modified kaolin to evenly disperse the modified kaolin in the water to obtain a modified kaolin dispersion for use.

[0017] As a further technical solution, the mass ratio of the modified kaolin to deionized water is 1:8-14.

[0018] As a further technical solution, the preparation of the modified kaolin comprises the following steps:

[0019] (1) dispersing nano-titanium dioxide and deionized water in deionized water at a ratio of 1:10-20 to obtain a nano-titanium dioxide dispersion;

[0020] (2) Adding polyethylene glycol and alkyl polyoxyethylene ether phosphate to the nano-titanium dioxide dispersion, ultrasonically dispersing for 10 to 12 minutes, adding kaolin dispersion, stirring for 30 to 50 minutes, and then washing by vacuum filtration, and finally vacuum drying the washed product at 30 to 40° C. to obtain preliminary modified kaolin;

[0021] (3) The kaolin that has undergone preliminary modification is placed in a corona device for corona treatment to obtain modified kaolin for later use.

[0022] As a further technical solution, the mass fraction of nano-titanium dioxide in the preliminary modified kaolin described in step (2) is 1-5%, the mass fraction of polyethylene glycol is 0.8-1.6%, the mass fraction of alkyl polyoxyethylene ether phosphate is 2.1-2.5%, and the balance is kaolin.

[0023] As a further technical solution, the preparation method of the kaolin dispersion described in step (2) is:

[0024] Kaolin and deionized water are mixed in a mass ratio of 1:10-20 using a magnetic stirrer to evenly disperse the kaolin in the water to obtain a kaolin dispersion.

[0025] As a further technical solution, the power of the corona treatment in step (3) is 4-5 kW, and the time of the corona treatment is 60-120 s.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] The present invention provides an SCR denitration process for treating phenylenediamine waste gas, wherein a reducing agent is injected into the flue gas upstream of the catalyst, and a modified kaolin-supported vanadium-titanium catalyst is used for SCR denitration to reduce NOx to harmless N 2 and H 2 O, significantly reducing the emission of NOx in the production of phenylenediamine, effectively improving the quality of the surrounding environment, especially for reducing the formation of acid rain and photochemical smog.

[0028] By introducing a modified kaolin-supported vanadium-titanium catalyst prepared by a specific method into the SCR denitration process, the denitration efficiency in the treatment of phenylenediamine exhaust gas can be significantly improved, and the denitration efficiency can reach 98.3%. The catalyst introduced by the present invention not only has good water resistance and sulfur resistance, but also exhibits good low-temperature catalytic activity and a wide temperature window, while well avoiding the situation where other particulate matter and other sulfides cause catalyst deactivation and poisoning. In order to further optimize the SCR denitration process, the present invention combines physical treatment methods with chemical processing techniques in the preparation of modified kaolin-supported vanadium-titanium catalysts, and the two work together to achieve better results.

[0029] First, polyethylene glycol and alkyl polyoxyethylene ether phosphate are added to the aqueous dispersion of nano titanium dioxide, and then the kaolin dispersion is added. After the hydrophobic main chain of polyethylene glycol contacts water, the hydrophobic part quickly self-aggregates to form aggregates, destroying the water molecule layer between the nano titanium dioxide particles, triggering the exposure of active groups, and improving the adhesion of nano titanium dioxide. At the same time, the alkyl polyoxyethylene ether phosphate is used to further activate the surface. In addition, the introduction of phosphorus can also increase the reaction rate and efficiency of the acidic center of kaolin and improve the catalytic activity of the catalyst at low temperatures. After stirring, vacuum filtration and washing, vacuum drying is performed under vacuum conditions, which can not only improve the stability of the modified kaolin but also improve the porosity. In order to further improve the performance of kaolin, corona treatment is carried out after drying. The plasma generated by the corona treatment can act on the treated kaolin, enhance the modification effect of polyethylene glycol, alkyl polyoxyethylene ether phosphate and nano-titanium dioxide on kaolin, and make the surface of kaolin rough, thereby increasing the specific surface area. Introducing it into the preparation of the catalyst helps to expose the active sites on the catalyst surface, thereby further improving the catalytic effect.

[0030] Secondly, the modified kaolin is introduced into the processing of the vanadium-titanium catalyst, which improves the pore structure of the vanadium-titanium catalyst, and increases its specific surface area, pore volume and average pore size, which means that the dispersion of the active sites on the catalyst surface increases, and the exposed active sites also increase, and the contact opportunities with gas molecules increase, which is conducive to improving the SCR activity, and the pore volume of the modified kaolin-supported vanadium-titanium catalyst of the present invention belongs to micropores, which are more conducive to the dispersion of active components, thereby further improving the denitration efficiency. In addition, the catalyst of the present invention has significant denitration performance in the medium and low temperature range, and the NO conversion rate reaches more than 95% at 250°C, which reduces the denitration cost to a certain extent.

[0031] The present invention not only provides a method for the SCR denitration process of phenylenediamine, but also provides a catalyst with high activity, high selectivity and high stability for the chemical industry. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0033] An SCR denitration process for treating phenylenediamine waste gas comprises the following steps:

[0034] Ammonia is injected into the flue gas upstream of the catalyst, and SCR denitrification is performed using a modified kaolin-supported vanadium-titanium catalyst.

[0035] The preparation method of the modified kaolin-supported vanadium-titanium catalyst is as follows:

[0036] Dissolve ammonium metavanadate in deionized water, stir for 1 h, then add TiO 2 The powder was fully stirred for 2 hours, then the modified kaolin dispersion was added, and the mixture was placed in an ultrasonic generator and ultrasonically treated at 80°C for 4 hours. After evaporating excess water, the mixture was placed in a muffle furnace and calcined at 500°C to obtain the modified kaolin-supported vanadium-titanium catalyst.

[0037] The mass fraction of ammonium metavanadate in the modified kaolin-supported vanadium-titanium catalyst is 3%, the mass fraction of modified kaolin is 8%, and the rest is TiO 2 ;

[0038] When ammonium metavanadate is dissolved, ethanolamine is added as a co-solvent.

[0039] The preparation method of the modified kaolin dispersion is:

[0040] Add the modified kaolin into distilled water, and use a magnetic stirrer to fully mix the modified kaolin to evenly disperse the modified kaolin in the water to obtain a modified kaolin dispersion for use.

[0041] The mass ratio of the modified kaolin to deionized water is 1:8.

[0042] The preparation of the modified kaolin comprises the following steps:

[0043] (1) dispersing nano-titanium dioxide and deionized water in deionized water at a ratio of 1:10 to obtain a nano-titanium dioxide dispersion;

[0044] (2) Adding polyethylene glycol and alkyl polyoxyethylene ether phosphate to the nano-titanium dioxide dispersion, ultrasonically dispersing for 10 minutes, adding kaolin dispersion, stirring for 30 minutes, washing by vacuum filtration, and finally vacuum drying the washed product at 30°C to obtain preliminary modified kaolin;

[0045] The preparation method of the kaolin dispersion is:

[0046] The kaolin and deionized water were mixed in a mass ratio of 1:10 using a magnetic stirrer to evenly disperse the kaolin in the water to obtain a kaolin dispersion;

[0047] The mass fraction of nano titanium dioxide in the preliminary modified kaolin is 1%, the mass fraction of polyethylene glycol is 0.8%, the mass fraction of alkyl polyoxyethylene ether phosphate is 2.1%, and the balance is kaolin;

[0048] (3) The kaolin after preliminary modification is placed in a corona device and treated with 4 kW corona for 60 seconds to obtain the modified kaolin for use. Example 2

[0049] An SCR denitration process for treating phenylenediamine waste gas comprises the following steps:

[0050] Ammonia is injected into the flue gas upstream of the catalyst, and SCR denitrification is performed using a modified kaolin-supported vanadium-titanium catalyst.

[0051] The preparation method of the modified kaolin-supported vanadium-titanium catalyst is as follows:

[0052] Dissolve ammonium metavanadate in deionized water, stir for 1.5 h, then add TiO 2 The powder was fully stirred for 2.5 hours, then the modified kaolin dispersion was added, placed in an ultrasonic generator, and ultrasonically treated at 80°C for 4.5 hours. After evaporating excess water, the mixture was placed in a muffle furnace and calcined at 550°C to obtain the modified kaolin-supported vanadium-titanium catalyst.

[0053] The mass fraction of ammonium metavanadate in the modified kaolin-supported vanadium-titanium catalyst is 3.5%, the mass fraction of modified kaolin is 10%, and the rest is TiO 2 ;

[0054] When ammonium metavanadate is dissolved, ethanolamine is added as a co-solvent.

[0055] The preparation method of the modified kaolin dispersion is:

[0056] Add the modified kaolin into distilled water, and use a magnetic stirrer to fully mix the modified kaolin to evenly disperse the modified kaolin in the water to obtain a modified kaolin dispersion for use.

[0057] The mass ratio of the modified kaolin to deionized water is 1:11.

[0058] The preparation of the modified kaolin comprises the following steps:

[0059] (1) dispersing nano-titanium dioxide and deionized water in deionized water at a ratio of 1:15 to obtain a nano-titanium dioxide dispersion;

[0060] (2) Adding polyethylene glycol and alkyl polyoxyethylene ether phosphate to the nano-titanium dioxide dispersion, ultrasonically dispersing for 11 minutes, adding kaolin dispersion, stirring for 40 minutes, washing by vacuum filtration, and finally vacuum drying the washed product at 35°C to obtain preliminary modified kaolin;

[0061] The preparation method of the kaolin dispersion is:

[0062] The kaolin and deionized water were mixed in a mass ratio of 1:15 using a magnetic stirrer to evenly disperse the kaolin in the water to obtain a kaolin dispersion;

[0063] The mass fraction of nano titanium dioxide in the preliminary modified kaolin is 3%, the mass fraction of polyethylene glycol is 1.2%, the mass fraction of alkyl polyoxyethylene ether phosphate is 2.3%, and the balance is kaolin;

[0064] (3) The kaolin after preliminary modification is placed in a corona device and treated with 4.5 kW corona for 90 seconds to obtain the modified kaolin for use. Example 3

[0065] An SCR denitration process for treating phenylenediamine waste gas comprises the following steps:

[0066] Ammonia is injected into the flue gas upstream of the catalyst, and SCR denitrification is performed using a modified kaolin-supported vanadium-titanium catalyst.

[0067] The preparation method of the modified kaolin-supported vanadium-titanium catalyst is as follows:

[0068] Dissolve ammonium metavanadate in deionized water, stir for 2 h, then add TiO 2 The powder was fully stirred for 2-3 hours, then the modified kaolin dispersion was added, and the mixture was placed in an ultrasonic generator and ultrasonically treated at 80°C for 4-5 hours. After evaporating excess water, the mixture was placed in a muffle furnace and calcined at 600°C to obtain the modified kaolin-supported vanadium-titanium catalyst.

[0069] The mass fraction of ammonium metavanadate in the modified kaolin-supported vanadium-titanium catalyst is 4%, the mass fraction of modified kaolin is 12%, and the rest is TiO 2 ;

[0070] When ammonium metavanadate is dissolved, ethanolamine is added as a co-solvent.

[0071] The preparation method of the modified kaolin dispersion is:

[0072] Add the modified kaolin into distilled water, and use a magnetic stirrer to fully mix the modified kaolin to evenly disperse the modified kaolin in the water to obtain a modified kaolin dispersion for use.

[0073] The mass ratio of the modified kaolin to deionized water is 1:14.

[0074] The preparation of the modified kaolin comprises the following steps:

[0075] (1) dispersing nano-titanium dioxide and deionized water in deionized water at a ratio of 1:20 to obtain a nano-titanium dioxide dispersion;

[0076] (2) Adding polyethylene glycol and alkyl polyoxyethylene ether phosphate to the nano-titanium dioxide dispersion, ultrasonically dispersing for 12 minutes, adding kaolin dispersion, stirring for 50 minutes, washing by vacuum filtration, and finally vacuum drying the washed product at 40°C to obtain preliminary modified kaolin;

[0077] The preparation method of the kaolin dispersion is:

[0078] The kaolin and deionized water were mixed in a mass ratio of 1:20 using a magnetic stirrer to evenly disperse the kaolin in the water to obtain a kaolin dispersion;

[0079] The mass fraction of nano titanium dioxide in the preliminary modified kaolin is 5%, the mass fraction of polyethylene glycol is 1.6%, the mass fraction of alkyl polyoxyethylene ether phosphate is 2.5%, and the balance is kaolin;

[0080] (3) Place the kaolin that has undergone preliminary modification in a corona device and perform a 5kW corona treatment for 120 seconds to obtain the modified kaolin for use.

[0081] Comparative Example 1

[0082] On the basis of Example 2, no modified kaolin dispersion is added, and the rest of the technical scheme is consistent with the technical scheme of Example 2.

[0083] Comparative Example 2

[0084] On the basis of Example 2, the modified kaolin dispersion was replaced with kaolin dispersion, and the rest of the technical scheme was consistent with that of Example 2.

[0085] Comparative Example 3

[0086] On the basis of Example 2, nano titanium dioxide is not added in the preparation of modified kaolin, and the rest of the technical scheme is consistent with the technical scheme of Example 2.

[0087] Comparative Example 4

[0088] On the basis of Example 2, polyethylene glycol is not added in the preparation of modified kaolin, and the rest of the technical scheme is consistent with the technical scheme of Example 2.

[0089] Comparative Example 5

[0090] On the basis of Example 2, no alkyl polyoxyethylene ether phosphate salt is added in the preparation of modified kaolin, and the rest of the technical scheme is consistent with the technical scheme of Example 2.

[0091] Comparative Example 6

[0092] On the basis of Example 2, no corona treatment is performed in the preparation of modified kaolin, and the rest of the technical scheme is consistent with the technical scheme of Example 2.

[0093] test

[0094] 1. Determination of specific surface area and pore structure of catalyst

[0095] Specific surface area (BET): by testing sample N 2 The adsorption-desorption curve was used to obtain the specific surface area and pore size distribution information of the sample. The TriStar Ⅱ3020 multi-channel specific surface area and pore size analyzer produced by Micromeritics Instruments Co., Ltd. was used to characterize the structural parameters such as catalyst surface area, pore size and pore size.

[0096] The test results are shown in Table 1 below:

[0097] Table 1 Pore structure parameters of catalysts corresponding to each embodiment and comparative example

[0098] Test items <![CDATA[Specific surface area (m 2 ·g -1 )]]> <![CDATA[Pore volume (cm 3 ·g -1 )]]> Average pore size (nm) Example 1 82.1 0.29 13.9 Example 2 83.5 0.30 14.2 Example 3 84.9 0.31 14.5 Comparative Example 1 52.3 0.16 9.8 Comparative Example 2 61.2 0.21 11.9 Comparative Example 3 76.9 0.24 13.2 Comparative Example 4 80.3 0.26 13.8 Comparative Example 5 81.0 0.28 12.5 Comparative Example 6 78.6 0.25 11.3

[0099] From the comparison of the experimental data in Table 1, it can be found that the modified kaolin-supported vanadium-titanium catalyst prepared in the present invention has excellent specific surface area, pore volume and average pore diameter, and the pore volume of the modified kaolin-supported vanadium-titanium catalyst of the present invention belongs to micropores, which are more conducive to the dispersion of active components, thereby helping to improve the denitrification efficiency.

[0100] From the comparison of the experimental data of Example 2 and Comparative Example 1, it can be found that the specific surface area, pore volume and average pore diameter of the catalyst in Example 2 are significantly larger than those in Comparative Example 1, indicating that the modified kaolin dispersion can significantly improve the specific surface area of ​​the vanadium-titanium catalyst, thereby facilitating the improvement of SCR activity.

[0101] From the comparison of the experimental data of Example 2 and Comparative Example 2, it can be found that the specific surface area, pore volume and average pore size of the catalyst in Example 2 are significantly superior to those in Comparative Example 2, which means that after the kaolin is modified, the specific surface area, pore volume and average pore size of the catalyst can be greatly increased, which means that it has a greater chance of contacting with gas molecules and the denitrification efficiency will be higher.

[0102] From the comparison of the experimental data of Example 2 and Comparative Examples 3, 4, and 5, it can be found that the catalyst specific surface area, pore volume, and average pore volume of Example 2 are improved compared with those of Comparative Examples 3, 4, and 5, and Comparative Examples 3, 4, and 5 are all weaker than Example 2, indicating that in the modification of kaolin, there is a certain synergistic effect between nano-titanium dioxide, polyethylene glycol, and alkyl polyoxyethylene ether phosphate, which synergistically act on kaolin to improve the pore structure and surface properties of kaolin.

[0103] From the comparison of the experimental data of Example 2 and Comparative Example 6, it can be found that the specific surface area and pore volume of the catalyst in Example 2 are better than those in Comparative Example 6, indicating that the plasma generated by the corona treatment can act on the treated kaolin to roughen the surface of the kaolin, thereby increasing the specific surface area, which helps to expose the active sites on the catalyst surface, thereby further improving the catalytic effect.

[0104] 2. Denitrification rate determination

[0105] A Fourier transform infrared spectrometer was connected to a gas cell to detect the changes in NO.

[0106] SCR reaction conditions: NO (volume fraction, 0.05%), NH 3 (volume fraction, 0.05%), O 2 (volume fraction, 5%), H 2 O (volume fraction, 5%), SO 2 (volume fraction, 0.01%), N 2 As balance gas, the total flow rate is 300mL min −1 , the reaction volume space velocity is 64000h −1 The data was collected at intervals of 50°C within the temperature range of 150-350°C to test the SCR reaction performance.

[0107] The NO conversion rate was calculated according to the following formula:

[0108]

[0109] Where: Q is NO conversion rate, %; C NO入 is the volume fraction of NO at the reaction inlet, %; C NO出 is the volume fraction of NO at the reaction outlet, %.

[0110] Table 2 NO conversion rate at different temperatures in various examples and comparative examples

[0111]

[0112] From the comparison of the test data in Table 2, it can be found that the modified kaolin-supported vanadium-titanium catalyst prepared in the present invention exhibits good low-temperature catalytic activity and a wide temperature window, and has significant denitration performance.

[0113] From the comparison of the experimental data of Example 2 and Comparative Examples 1 and 2 in Table 2, it can be found that compared with Comparative Examples 1 and 2, the corresponding catalyst of Example 2 has significant denitration performance in the medium and low temperature range, and the NO conversion rate reaches more than 95% at 250°C, and the effect of Comparative Example 2 is better than that of Comparative Example 1, which shows that the introduction of modified kaolin dispersion can well improve the activity of vanadium titanium catalyst and promote the conversion of NO. It also shows that although kaolin has a large specific surface area and good adsorption properties, its introduction into vanadium titanium catalyst can improve the catalytic activity, but due to the limited porosity of kaolin as a carrier and the disadvantages of instability when exposed to water, the direct introduction of kaolin does not significantly improve the catalytic activity, and may also reduce the stability of the catalyst and shorten the service life of the catalyst.

[0114] From the comparison of the experimental data of Example 2 and Comparative Examples 3, 4, 5, and 6 in Table 2, it can be found that compared with Comparative Examples 3, 4, and 5, the corresponding catalyst of Example 2 has significant denitration performance in the medium and low temperature range, and the NO conversion rate reaches more than 95% at 250°C. It is also found that there are certain differences in the NO conversion rates among Comparative Examples 3, 4, 5, and 6, which shows that nano-titanium dioxide, polyethylene glycol, and alkyl polyoxyethylene ether phosphate can synergistically act with each other and cooperate with the effect of corona to increase the porosity of kaolin, thereby improving the stability of kaolin on the basis of improving the activity of the modified kaolin-supported vanadium-titanium catalyst.

[0115] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An SCR denitration process for treating phenylenediamine waste gas, characterized in that: The following steps are involved: A reducing agent is sprayed into the flue gas upstream of the catalyst, and SCR denitration is performed using a modified kaolin-supported vanadium-titanium catalyst; the reducing agent is ammonia; The preparation method of the modified kaolin-supported vanadium-titanium catalyst is as follows: Dissolve ammonium metavanadate in deionized water, stir for 1-2 hours, then add TiO2 powder, stir thoroughly for 2-3 hours, then add modified kaolin dispersion, put into an ultrasonic generator, perform ultrasonic treatment at 80°C for 4-5 hours, evaporate excess water, then place in a muffle furnace and calcine at 500-600°C to obtain a modified kaolin-supported vanadium-titanium catalyst; The preparation method of the modified kaolin dispersion is: Add the modified kaolin to distilled water, and use a magnetic stirrer to fully mix, so that the modified kaolin is evenly dispersed in the water to obtain a modified kaolin dispersion for use; The preparation of the modified kaolin comprises the following steps: (1) dispersing nano-titanium dioxide and deionized water in deionized water at a ratio of 1:10 to 20 to obtain a nano-titanium dioxide dispersion; (2) adding polyethylene glycol and alkyl polyoxyethylene ether phosphate to the nano-titanium dioxide dispersion, ultrasonically dispersing for 10 to 12 minutes, adding the kaolin dispersion, stirring for 30 to 50 minutes, and then washing by vacuum filtration and washing, and finally vacuum drying the washed product at 30 to 40° C. to obtain preliminary modified kaolin; (3) Placing the kaolin after the preliminary modification treatment in a corona device and performing corona treatment to obtain the modified kaolin for use.

2. The SCR denitration process for treating phenylenediamine waste gas according to claim 1, characterized in that: The mass fraction of ammonium metavanadate in the modified kaolin-supported vanadium-titanium catalyst is 3-4%, the mass fraction of modified kaolin is 8-12%, and the rest is TiO2; When ammonium metavanadate is dissolved, ethanolamine is added as a co-solvent.

3. The SCR denitration process for treating phenylenediamine waste gas according to claim 1, characterized in that: The mass ratio of the modified kaolin to distilled water is 1:8-14.

4. The SCR denitration process for treating phenylenediamine waste gas according to claim 1, characterized in that: The mass fraction of nano-titanium dioxide in the preliminary modified kaolin described in step (2) is 1-5%, the mass fraction of polyethylene glycol is 0.8-1.6%, the mass fraction of alkyl polyoxyethylene ether phosphate is 2.1-2.5%, and the balance is kaolin.

5. The SCR denitration process for treating phenylenediamine waste gas according to claim 1, characterized in that: The preparation method of the kaolin dispersion described in step (2) is: Kaolin and deionized water are mixed in a mass ratio of 1:10 to 20 using a magnetic stirrer to evenly disperse the kaolin in the water to obtain a kaolin dispersion.

6. The SCR denitration process for treating phenylenediamine waste gas according to claim 1, characterized in that: The power of the corona treatment in step (3) is 4-5 kW, and the time of the corona treatment is 60-120 s.

Citation Information

Patent Citations

  • SCR denitration catalyst and preparation method thereof

    CN104399453A

  • Low-temperature SCR denitration catalyst based on kaoline and preparation method of catalyst

    CN110314681A